Detection of the binary companion to the progenitor of SN 1993J - Smartt, S; Maund, JR; Kudritzki, R; Podsiadlowski, P; Gilmore, G (2005)
We present a detailed late-time photometric and spectroscopic study of SN1993J with HST/ACS and Keck LRIS-B. We find a clear signature of a hot star component in the spectra of SN1993J which cannot be explained by the surrounding faint blue stars. This is the first detection of the expected massive binary companion to the red supergiant progenitor and confirms that SN1993J did indeed arise in an interacting binary system.